The role of expansion joints for traditional buildings affected by the curvature of the mining area. (October 2021) - Kapusta, Łukasz; Szojda, Leszek
Highlights: Underground mining of minerals causes surface deformations that affect buildings. Objects not adapted to transfer additional loads may be damaged or even fall. Analysis of soil-structure interaction enables to determine the internal forces of structure. Results of numerical analysis confirm the behavior of the actual building structure. Abstract: The work presents the impact of mining exploitation on residential buildings located in Bytom - in Silesian Voivodeship, in the south of Poland. This is one of the most interesting mining areas in the country. Exploitation works performed here for several decades still give the opportunity to study in a wide range the negative impact of mining activities on buildings. The research focused mainly on the impact of the variable curvature of the mining area on two multi-family residential buildings with similar construction characteristics, erected at the beginning of the last century in traditional brick technology. These objects similar in terms of construction details differ essentially in that the first one is divided by expansion joints while the second one is built continuously, without expansion joints. Both buildings were monitored geodesically during the passage of the exploitation front under them. The measuring work lasted over two years. Based on the observations carried out, the time-varying, real dependence between the size of building deformations and the surface area in their vicinity was obtained. The obtained results were the source data for numerical analyzes capturing the impact of the deforming mining area on the state of stress in the structure of objects. The main purpose of the analyzes was to illustrate the role of expansion joints in buildings subjected to the influence of curvature of the mining origin.